Pengaruh Employee Engagement terhadap Kinerja Karyawan Program Diploma III di Fakultas Ekonomi Universitas Islam Indonesia - Rizqi Adhyka Kusumawati (Jurnal Maksipreneur, 2017)
This research aims to study the independent variable (employee engagement) that affects employee performance in a positive and significant way. The questionnaire used in this research is a questionnaire that has been adapted to the theory of analysis used. The overall statement in the questionnaire is a favorable statement with 13 respondents who are all employees of D-3 Program in Faculty of Economics of Islamic University of Indonesia (UII). The results of multiple linear regression analysis show that employee engagement variable influence employee performance with a positive, but not significant way. It can be seen from the results of the F-test that shows Fcount<Ftabel (6.15 <8.81) and shown by the value of coefficient of determination (R2) of 0.969. The result of t-test gives all factors in employee engagement variable does not affect employee performance variable and collaborate factor is not dominant factor influence employee performance, whereas convey factor has the biggest influence to employee performance according to coefficient value.